(untitled) (Al-Wasatiyah: Journal of Religious Moderation, 2024)
Societalorganization (Ormas in Indonesian) are considered to have a significant role in campaigning for moderation in the current digital era. This is proven by the number of Islamic websites owned by mass organizations, in which there are always moderation narratives, such as two sites owned by Muhammadiyah mass organisations that have the highest ratings, namely muhammadiyah.or.id and ibtimes.id. This research wants to further examine how the two sites build framing of moderation news in Indonesia by using netnography research method tools. To dissect this, this research uses Robert M. Puntman’s Framing theory, which goes through four stages of the analysis process, 1. define problem, 2. diagnose cause, 3. make moral judgement, 4. treatment recommendation. The result of this study based on the five news articles analyzed by the researchers is that the framing built by the muhamadiyyah.or.id and ibtimes.id sites are very moderate and in line with the reality of Indonesian society from various aspects, both religious, social, and cultural, as well as in line with the spirit of nationalism.